(Re) assumindo a raiz: a discursivização sobre a mulher negra a partir da noção de cabelos crespos, presente nas comunidades do facebook - Boa Morte, Cláudia Maísa Pinheiro da (2017)
What are the senses’ effects generated on black women from the notion of nappy hair on hair-focused Facebook communities? This questioning drives this research, which seeks to answer the question under Pêcheux’s Discourse Analysis theoretical contribution. The proposal is to present the aspects related to the concepts of senses, ideological formation, discursive formation, interdiscourse, discursive memory and silencing, elements that are intrinsic to the notion of discourse and to the subjects that are discussed on Facebook communities. Black women occupy the place of the discourse’s object, which produces and reproduces senses based on certain conditions of production. Thus, on Facebook there is a competition between different discursive formations, allowing the resumption, resignification and rupture of historically constructed meanings about black women and beauty standards. Through the posts and comments on chosen communities, it was analyzed how social, historical and ideological issues permeate the discourses about the black women subject and the process of acceptance and / or rejection of nappy hair in the virtual environment, which reflects, in many aspects, what is present in the real environment. Senses that are attributed to hair do not refer only to the aesthetic, but to the way the image of the black women was socially constituted.